Mortality among elder abuse victims in rural Malaysia: A two-year population-based descriptive study - Yunus, R.M.; Hairi, N.N.; Choo, W.Y.; Hairi, Farizah Mohd; Sooryanarayana, R.; Ahmad, S.N.; Razak, I.A.; Peramalah, D.; Aziz, S.A.; Mohammad, Z.L.; Mohamad, R.; Ali, Z.M.; et al. (Haworth Press, 2017)
Our study aims at describing mortality among reported elder abuse experiences in rural Malaysia. This is a population-based cohort study with a multistage cluster sampling method. Older adults in Kuala Pilah (n = 1,927) were interviewed from November 2013 to May 2014. Mortality was traced after 2 years using the National Registration Department database. Overall, 139 (7.2%) respondents died. Fifteen (9.6%) abuse victims died compared to 124 (7.0%) not abused. Mortality was highest with financial abuse (13%), followed by psychological abuse (10.8%). There was a dose-response relationship between mortality and clustering of abuse: 7%, 7.7%, and 14.0% for no abuse, one type, and two types or more, respectively. Among abuse victims, 40% of deaths had ill-defined causes, 33% were respiratory-related, and 27% had cardiovascular and metabolic origin. Results suggest a link between abuse and mortality. Death proportions varied according to abuse subtypes and gender.